2010
DOI: 10.1007/s12070-010-0010-z
|View full text |Cite
|
Sign up to set email alerts
|

The selection and strategy in otoendoscopic myringoplasty with autogenous adipose tissue

Abstract: Otoendoscopic myringoplasty with adipose tissue is a simple and minimally invasive technique for tympanic membrane perforations. With optimal choice at indication and correct treatment to complication, the technique will give the advantages of slighter trauma, simpler procedure, lower cost and reduced complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Deddens et al (6) and Konstantinidis et al (2) reported that TMP size is a critical factor affecting success rate, and they recommend that fat myringoplasty should be applied when the TMP size is less than 30% of the TM. Li et al (7), Kim et al (5), Gun et al (9,10), and Konstantinidis et al (2) showed poor success rate for large perforations, but Knutsson et al (10) reported a higher success rate for large perforations than for small perforations. In this study, the success rate was not proportional to the size of the TMP.…”
Section: Discussionmentioning
confidence: 99%
“…Deddens et al (6) and Konstantinidis et al (2) reported that TMP size is a critical factor affecting success rate, and they recommend that fat myringoplasty should be applied when the TMP size is less than 30% of the TM. Li et al (7), Kim et al (5), Gun et al (9,10), and Konstantinidis et al (2) showed poor success rate for large perforations, but Knutsson et al (10) reported a higher success rate for large perforations than for small perforations. In this study, the success rate was not proportional to the size of the TMP.…”
Section: Discussionmentioning
confidence: 99%
“…Deddens et al [6], and Konstantinidis et al reported that TM perforation size is a critical factor for success rate and they recommend that fat myringoplasty should be applied when the TM perforation size is less than 30% of TM. Li et al [7], Kim et al [5], Gun et al [26], and Konstantinidis et al [2] showed poor success rate in large perforation but Knutsson et al [10] reported higher success rate in large perforation than small perforation. In this study, it was not proportional to the size of the TM perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Since Ringerberg [1] introduced for the first time, it has been accepted successful technique for small TMP and geriatric patients [2][3][4]. According to the publicated reports, average success rate of fat myringoplasty has been reported from 72.9% to 92.2% [2,[5][6][7][8][9][10]. Recently, Salabi et al introduced that the fat myringoplasty with hyaluronic acid (Epidisc Otologic Lamina; Xomed-Medtronic, Jacksonville, FL) enhanced the success rate compared to simple fat myringoplasty as well small perforation as large perforation of the tympanic membrane [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports of studies limited to investigations of small perforations report success rate >80% like our study. 11,[20][21][22][23] Many researchers have demonstrated appropriate indications or conditions for fat myringoplasty. 1,3,10,21) We summarize 2 sets of representative criteria.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with those of previous studies comparing surgical outcomes between pure-fat myringoplasty and fat myringoplasty with HA 25) as well as those solely reporting outcomes associated with pure-fat myringoplasty. 10,[21][22][23][25][26][27] PRP is an autologous blood product that includes many concentrated autologous growth factors and essential proteins for tissue regeneration; therefore, some researchers have believed that PRP has the potential to not only promote healing of TM perforations and prevent TM dehydration but also stimulate centripetal migration of the outer epithelial layer. 13,20) With these characteristics of PRP, some researchers have documented that fat myringoplasty with PRP allows TM closure success rates exceeding 85%, 13,14) reporting higher success rate than those associated with pure-fat myringoplasty.…”
Section: Discussionmentioning
confidence: 99%